CRISPR-TAPE: protein-centric CRISPR guide design for targeted proteome engineering. - Anderson,DP; Benns,HJ; Tate,EW; Child,MA (Mol Syst Biol, 2020)
Rational molecular engineering of proteins with CRISPR-based approaches is challenged by the gene-centric nature of gRNA design tools. To address this, we have developed CRISPR-TAPE, a protein-centric gRNA design algorithm that allows users to target specific residues, or amino acid types within proteins. gRNA outputs can be customized to support maximal efficacy of homology-directed repair for engineering purposes, removing time-consuming post hoc curation, simplifying gRNA outputs and reducing CPU times.